Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-05-01T14:36:41+02:00
A= 4*-3-5
A= -17

B= -2(y+3)
B= -2(4,5+3)
B= -15

C= 2x²+3x-2
C= 2*(-5)²+3*(-5)-2
C= 33
2014-05-01T14:37:02+02:00
A. Calcule la valeur de l'expression A= 4x - 5 pour x = -3
A=4*(−3) − 5
A= −12 − 5
A=−17

b. Calcule la valeur de l'expression B= -2(y + 3) pour y = 4.5
B= −2(4,5+3)
B=−2*7,5
B=−15

c. Calcule la valeur de l'expression C= 2x² + 3x -2 pour x = -5
C= 2*(−5)² + 3*(−5) − 2
C= 2*25 − 15 − 2
C= 50 − 15 − 2
C=33